Manajemen sarana prasarana pendidikan dalam meningkatkan kepuasan civitas akademik MI Roudlotul Huda Lampung Tengah - Lutfiyah, Binti; Fauzan, Ahmad; Junaidah, Junaidah; Masayu, Sovia; Wuryan, Siti; Anwar, Muhammad Saidun (Kuras Institute, 2023)
This study aims to examine the role of management of educational facilities and infrastructure in increasing the satisfaction of madrasah residents in Madrasah Ibtidaiyah Roudlotul Huda Purwosari Padang Ratu, Central Lampung. The research method used is descriptive with data collection techniques through questionnaires and interviews. The respondents in this study were madrasah residents consisting of students, teachers, and madrasah staff. The results showed that the management of educational facilities and infrastructure has an important role in increasing the satisfaction of madrasah residents. The availability of adequate educational facilities and infrastructure such as classrooms, libraries, laboratories, sports facilities, and canteens that are clean and comfortable greatly affects the satisfaction of madrasah residents. In addition, good management in the management of educational facilities and infrastructure such as maintenance, repair, and development of facilities also plays a role in increasing the satisfaction of madrasah residents. In this case, cooperation between madrasah administrators and related parties such as the government and the community is also very important to obtain support in the development of educational facilities and infrastructure. In conclusion, this study shows that the management of educational facilities and infrastructure has a very important role in increasing the satisfaction of madrasah residents. Therefore, efforts need to be made to improve the quality of educational facilities and infrastructure and their management to achieve these goals.